Coping, connection appraisal, and well-being during COVID-19 in the U.S., Japan, and Mexico - Benjamin, Laurel R.; Wang, Shu-wen (Frontiers in Psychology, 2024)
Introduction The COVID-19 pandemic has affected nearly every facet of life, constituting a “new normal” and prompting an ongoing collective psychological crisis. People’s ways of coping with the pandemic and corresponding well-being are of particular research interest; however, these constructs have largely been examined using deductive quantitative approaches, deficit-based lenses, and mononational samples. Methods The current mixed-methods study used inductive-sequential (QUAL → QUAN) approaches to explore positive coping strategies (approach coping style and COVID-related connection appraisal) and well-being (loneliness, distress, and happiness) across individuals from the United States, Japan, and Mexico. Qualitative data were gathered from N = 141 U.S., Japanese, and Mexican adults to examine how people perceived connection during the pandemic. Results Qualitative analyses illuminated common themes in which people appraised the pandemic as an opportunity for connection and strengthened interpersonal relationships. Quantitative measures, including a newly-developed questionnaire on COVID-related connection appraisal, were then administered to a separate sample of N = 302 adults in the U.S, Japan, and Mexico to assess associations among approach coping style, COVID-related connection appraisal, and well-being outcomes (loneliness, distress, happiness). Quantitative analyses found significant associations among approach coping style, COVID-related connection appraisal, and all well-being outcomes. Of note, these associations did not differ by country. COVID-related connection appraisal mediated the relationship between approach coping style and two well-being outcomes (loneliness and happiness). Discussion Findings point to approach coping style and connection appraisal as pathways for resilience and growth in the face of global suffering.